2003
DOI: 10.1177/03635465030310042001
|View full text |Cite
|
Sign up to set email alerts
|

Low Regional Tibial Bone Density in Athletes with Medial Tibial Stress Syndrome Normalizes after Recovery from Symptoms

Abstract: Athletes with medial tibial stress syndrome and increased scintigraphic uptake regain normal tibial bone mineral density after recovery from symptoms. Initially localized low bone mineral density is not an inherited condition, but instead may develop in conjunction with the symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Bone scans, x-ray, Doppler US and compartment pressure tests are used to differentiate MTSS from compartment syndrome, popliteal artery entrapment syndrome and frank stress fracture. The syndrome is thought to include periostitis, bone stress and/or musculotendinous breakdown, although there is conflict in the literature as to which of these elements is most consistently a source of pain, with the weight of literature appearing to favour bone stress reaction 5 6. The adaptive capacity of bone in response to loading through mechanical stimuli has long been understood and described (Wolff's Law) 11 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone scans, x-ray, Doppler US and compartment pressure tests are used to differentiate MTSS from compartment syndrome, popliteal artery entrapment syndrome and frank stress fracture. The syndrome is thought to include periostitis, bone stress and/or musculotendinous breakdown, although there is conflict in the literature as to which of these elements is most consistently a source of pain, with the weight of literature appearing to favour bone stress reaction 5 6. The adaptive capacity of bone in response to loading through mechanical stimuli has long been understood and described (Wolff's Law) 11 14…”
Section: Introductionmentioning
confidence: 99%
“…Flexor muscles of the foot, toes and ankle also have some attachment here and likely add to loading of the bone–muscle interface. Measurable reductions in bone density at the site of injury can be present for up to 7 years postonset of symptoms 5. Left untreated the condition can progress to full stress fracture 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that at the injury site, male athletes with chronic MTSS had localised decreased BMD, and this reduction was bilateral even when the injury was unilateral. Additionally, they found that BMD normalises after recovery from the injury (Magnusson et al, 2003). At other sites of the tibia, the MTSS patients had higher BMD than the control group but lower BMD than the athletic control group.…”
Section: Bone Mineral Density In Tibial Sf and Mtss Patientsmentioning
confidence: 97%
“…It is now evident that MTSS involves alterations to at least the cortical bone of the tibia (Johnell et al, 1982;Magnusson et al, 2001;Magnusson et al, 2003;Franklyn et al, 2008;Murrihy, 2009), although whether the trabecular bone is also involved is unknown. This was first evident in the study by Johnell et al (1982), where cortical bone and soft tissue biopsies were obtained from control (non-injured) patients and patients with chronic MTSS.…”
Section: Bone Alterations Due To Injurymentioning
confidence: 99%
“…Recent studies showed that with overloaded remodelling the cortex appears osteopaenic on CT scans and that dual energy x-ray absorptiometry scans reveal decreased bone density 10 11. When MTSS symptoms subside the bone density returns to normal values,12 suggesting that MTSS is related to mechanical overloading of the bone.…”
mentioning
confidence: 99%